Limitations in Activity and Participation experienced by stroke patients : A Qualitative Inquiry - A. Rhoda (AOSIS, 2012)
Stroke affects individuals in a number of ways. The InternationalClassification of Functioning, Disability and Health can be used to conceptualizedisability post stroke. This framework not only identifies the factors as it relatesto disability but also highlights the conceptual factors which impacts on theindividual's ability to function. Within the framework of the ICF, the aim of thestudy was therefore to explore the activity limitations and participation restrictionsexperienced by patients with a stroke. A qualitative approach was used to interviewa convenient sample of 8 participants who were living in the community. A semistructuredinterview was conducted to obtain the data. The findings reveal that the participants had impairments of bodyfunctions of both the upper and lower limb. They experienced limitations in activities such as caring for themselves andmobility and were restricted in their ability to fulfill roles such work and caring for family. The factors which influencedthe above were personal factors such as impairments and environmental factors such as family and therapy. This studyprovides valuable qualitative information that could be used by health care professionals when providing rehabilitationservices to people with stroke aimed at reintegration back into the community.